On optimal stopping as game - Morkvėnas, R.; Pragarauskas, H. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Морквенас, Г. Прагараускас. К игровому варианту задачи об оптимальной остановке R. Morkvėnas, H. Pragarauskas. Optimalaus stabdymo uždavinys kaip lošimas